Isolamento e caracterização de inulina a partir de raízes de Stevia rebaudiana (Bertoni) Bertoni - Lopes, Sheila Mara Sanches (2012)
Stevia rebaudiana (Bertoni) Bertoni belongs to the Asteraceae family, its leaves are used by industry to obtain the steviol glycosides that have great commercial interest. Regarding primary metabolites, few studies which report the isolation and identification of this class of compound from S. rebaudiana. Inulin is a reserve polysaccharide very important because of its numerous technological applications. In the pharmaceutical industry it is used as a coating of pharmaceutical dosage forms for controlled drug delivery. In the food industry fat and sugar substitutes in low-calorie foods and nutritional action of dietary fiber and prebiotic. In the biofuel industry is used as substrate for the production of bioethanol. All applications are related to the degree of polymerization of the inulin molecule, according to the average chain length, the inulins have different properties, such as digestibility, viscosity, sweetening power and ability to bind to water. The objective of this study is to isolate, quantify and characterize the fructo-oligosaccharides in roots of Stevia rebaudiana, aiming to produce inulin with a high degree of polymerization that has greater interest and commercial value. The inulin were obtained from the aqueous extract of the roots of S. rebaudiana. Characterization of the extract was made from chemical and enzymatic assays and also by nuclear magnetic resonance of hydrogen and carbon-13. It was observed a yield of extraction of 29.31% which is higher than that observed from the main commercially available sources (15-20%). The molecules of crude inulin obtained from roots of S. rebaudiana showed a high DP (- 30) and inulins are rarer, since the main sources of presenting low DP (11-15). From the methodology freeze / defrosting for obtaining inulin high mass, it was possible to obtain fractions with different solubilities and DP supernatant (21-22) and precipitated (35-40). Therefore, the roots of Stevia rebaudiana represent a promising new source in obtaining commercial inulin with a high degree of polymerization that are more commercially important and there is a possibility of use as a byproduct of producing industry sweetener.